Sir James Lighthill and modern fluid mechanics: a memorial tribute - Lokenath Debnath (International Journal of Mathematics and Mathematical Sciences)
This memorial tribute commemorates Sir James Lighthill the man and the mathematical scientist. A brief biographical information is presented with my personal reminiscences. His major contributions to fluid mechanics with special reference to nonlinear dispersive waves are discussed. By any standards, his legacy of research and publications of six books and one hundred fifty papers will remain forever as a remarkable example of scholarly work.